2007
DOI: 10.1042/bj20061489
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the specificity of the PI3K family inhibitor LY294002

Abstract: The PI3Ks (phosphatidylinositol 3-kinases) regulate cellular signalling networks that are involved in processes linked to the survival, growth, proliferation, metabolism and specialized differentiated functions of cells. The subversion of this network is common in cancer and has also been linked to disorders of inflammation. The elucidation of the physiological function of PI3K has come from pharmacological studies, which use the enzyme inhibitors Wortmannin and LY294002, and from PI3K genetic knockout models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
278
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(293 citation statements)
references
References 56 publications
8
278
0
4
Order By: Relevance
“…Although LY294002 possesses an 'off-target' effect on casein kinase II (Gharbi et al 2007), 4,5,6,7-tetrabromobenzotriazole, a selective casein kinase II inhibitor, did not increase the Nis mRNA in FRTL-5 cells (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LY294002 possesses an 'off-target' effect on casein kinase II (Gharbi et al 2007), 4,5,6,7-tetrabromobenzotriazole, a selective casein kinase II inhibitor, did not increase the Nis mRNA in FRTL-5 cells (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…LY294002, however, also interacts many cellular proteins and inhibits some other kinases, such as casein kinase II, Pim-1 kinase, glycogen synthase kinase 3, and the 97 kDa valosin-containing protein (Gharbi et al 2007). To investigate whether the effect of LY294002 on iodide uptake is dependent on PI3K inhibition, we characterized the effect of LY294002 on iodide uptake in FRTL-5 cell compared with LY303511, an inactive analogue of LY294002, as well as another pan-PI3K inhibitor Wortmannin and a class 1 PI3K p110a (PI3KCA)-selective inhibitor PI-103 (Knight et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…2), a synthetic PI3K inhibitor whose structure is based on the naturally occurring flavonoid quercetin [79]. LY294002 behaves as a competitive inhibitor for the ATP-binding site and is much less potent against class I PI3Ks than wortmannin (IC 50~0 .3-4 μM) [80]. However, its superior chemical stability in solution has led to its widespread use as a PI3K inhibitor in cell-based experiments, where it is usually used at concentrations of 10-50 μM.…”
Section: Mtor Kinase Inhibitorsmentioning
confidence: 99%
“…Despite its frequent description as a "specific" PI3K inhibitor, LY294004 blocks the activity of a number of different protein kinases unrelated to PI3K [81]. In addition, use of immobilized LY294002 showed that the drug binds tightly to numerous non-kinase proteins with diverse functions, with as yet unknown biological consequences [80]. Class II PI3Ks (IC 50 =6.9-19 μM) and PI4Ks are relatively resistant to LY294002 as compared with the class I enzymes [60,61].…”
Section: Mtor Kinase Inhibitorsmentioning
confidence: 99%
“…PMNs express several PI3K isoforms, including PI3Kd and PI3Kg, which have different biological activities. Not only is LY294002 not selective for different PI3K isoforms, it also has activities on other lipid kinases and other unrelated proteins such as NF-kB, which is activated in leukocytes in patients with COPD (12). PI3K-independent motility responses have also been reported in human PMNs (13).…”
Section: The Practice Of Medicine: Insights and Updatesmentioning
confidence: 86%